2021
DOI: 10.1016/j.mayocp.2021.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Post–COVID-19 Syndrome (Long Haul Syndrome): Description of a Multidisciplinary Clinic at Mayo Clinic and Characteristics of the Initial Patient Cohort

Abstract: Objective To describe characteristics of a series of patients reporting prolonged symptoms after an infection with COVID-19. Methods This study describes the multidisciplinary COVID-19 Activity Rehabilitation Program (CARP), established at Mayo Clinic to evaluate and treat post-COVID-19 syndrome (PCS) patients, and reports the clinical characteristics of the first 100 patients receiving evaluation and management during the timeframe of June 1, 2020 and December 31, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
121
4
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 38 publications
13
121
4
6
Order By: Relevance
“…A recent longitudinal prospective cohort study of post-COVID-19 patients found that 30% had at least one symptom persisting for nine months or longer. 5 The sequelae of COVID-19 are referred to as “post-COVID syndrome” or “COVID long haul syndrome.” 6 However, in our analysis, the relationship between being diagnosed with COVID-19 and unemployment remained significant even after adjusting for self-rated health; thus, poor health may not be the reason for unemployment.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent longitudinal prospective cohort study of post-COVID-19 patients found that 30% had at least one symptom persisting for nine months or longer. 5 The sequelae of COVID-19 are referred to as “post-COVID syndrome” or “COVID long haul syndrome.” 6 However, in our analysis, the relationship between being diagnosed with COVID-19 and unemployment remained significant even after adjusting for self-rated health; thus, poor health may not be the reason for unemployment.…”
Section: Discussioncontrasting
confidence: 60%
“…Given the clinical context of the COVID-19 pandemic, with a greater prevalence of patients >65 years particularly among those requiring hospitalization, assessment of frailty status could be implemented prior to discharge and in early follow-up, to identify those individuals at higher risk of long-term persisting symptoms and, possibly, of incident disability. As a case in point, patients discharged with COVID-19 with symptoms including mood disorders, fatigue, and perceived cognitive impairment at 3 months had more difficulties on resumption of functional and occupational activities [25] . Thus, assessment of functional status could be a proxy to further clinical and social evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…Following recovery from the acute infection with SARS-CoV-2, many individuals have experienced a range of persistent symptoms of varied frequency and severity. Recovery is seldom linear and is, instead, characterised by recurrent exacerbations of new and existing symptoms, primarily shortness of breath and fatigue [ 15 ]. Participants in the present study reported that the burden of managing the ongoing effects of COVID-19 has a profound impact on all aspects of their life, including work, leisure, and ADL.…”
Section: Discussionmentioning
confidence: 99%